Supplementation of Corn-Soybean Based Broiler’s Diets with Different Levels of Acid Protease - Yadav, JL; Sah, RA (Journal of the Institute of Agriculture and Animal Science, 2005)
A study was conducted at the Animal Science Farm, Tuntungin, Putho of the Institute of Animal Science, University of the Philippines, Los Baños, College, Laguna, Philippines, during 2001-2002 to find out the supplementation effects of corn-soybean based broiler’s diet with acid protease on its performance. The parameters studied were: growth, feed consumption, nutrient digestibility and economic analysis. Three hundred day-old, male broiler chicks were group brooded and fed with commercial pre-starter diets for seven days. Thereafter the chicks were randomly distributed to 30 cages with 10 chicks each. Five treatments randomly assigned to the 30 cages using a Completely Randomized Design. The treatments were: basal diet, diet with reduced crude protein, diet with reduced crude protein + 0.05 % protease, diet with reduced crude protein + 0.075 % protease, and diet with reduced crude protein + 0.1 % protease. The body weight gain, feed consumption, feed efficiency, and carcass quality were recorded. The results showed that one per cent reduction in CP of the diet significantly decreased the crude protein digestibility of broiler starter and finisher diets. Although the protease supplementation of reduced CP diet consistently and significantly improved the digestibility of CP in broiler starter and finisher diets. Dietary protease inclusion at 0.075 percent significantly improved mean body weight gain in broiler at 28 days of age. Average cumulative feed consumption was significantly lower at 0.05 percent protease supplementation in broiler finisher diet. The highest income was derived from broilers fed diet supplemented with 0.075 percent protease. Further research should be carried out to confirm the results. Key words: Broiler, corn-based, and acid protease J. Inst. Agric. Anim. Sci. 26:65-70 (2005)